Antifungal Potential of Phytochemicals against Mauginiella scaettae, the Plant Pathogen Causing Inflorescence Rot of Date Palm. (8th March 2021) - Bouhlali, Eimad Dine Tariq; Derouich, Mgal; Meziani, Reda; Essarioui, Adil
Abstract : Date palm ( Phoenix dactylifera L.) inflorescence rot caused by Mauginiella scaettae poses a serious threat to date palm in Morocco. The present study aims to determine the antifungal activity of five plant extracts against M. scaettae, including Acacia cyanophylla, Cupressus atlantica, Eucalyptus torquata, Nerium oleander, and Schinus molle and link this effect to their content in phenolics and flavonoids, as well as their antioxidant properties. Plant extracts exhibited significant discrepancies regarding their antifungal activity (p < 0.05 ). The extracts of E. torquata and C. atlantica had the strongest and dose-dependent manner inhibitory effect against mycelial growth and spore germination. E. torquata and S. molle caused the greatest sporulation reductions of about 88.05% and 36.11%, respectively. In addition, there were significant differences among the examined plant extracts with respect to their total polyphenols (14.52–76.68 mg GAE/g DW), flavonoids (8.75–57.78 g RE/100 g DW), and antioxidant properties as measured by TEAC (74.77–391.23 mmol TE/g DW) and FRAP assays (87.18–474.04 mmol TE/g DW). Strong correlations were found between phenolic compounds and antioxidant activity suggesting that polyphenols play a key role in the observed antioxidant and antifungal activities.